Regulatory T Cell Counts and Development of Malignancy in Patients with HIV Infection - Politou, Marianna; Boti, Sofia; Androutsakos, Theodoros; Kontos, Athanasios; Pouliakis, Abraham; Kapsimali, Violetta; Panayiotakopoulos, George; Kordossis, Theodore; Karakitsos, Petros; Sipsas, Nikolaos V. (Current HIV Research, 2020)
Background: T-regulatory cells (Tregs) play an important role in maintaining homeostasis by attenuating the cytokine response to T-cell receptor (TCR) stimulation and by suppressing the functioning of neighboring immune cells. In Human Immunodeficiency Virus (HIV) infection, Tregs can be either beneficial, by suppressing generalized T-cell activation, or detrimental, by suppressing protective anti-HIV cell-mediated immunity. An imbalance of Tregs and effector T-cells can blunt immune responses to malignant cells or facilitate inflammation-mediated pathologies. Objective: The purpose of our study was to explore the possible correlation between Tregs’ concentration and HIV infection’s parameters as well as the development of hematological and solid malignancies. Methods: In a longitudinal prospective study, ex vivo phenotyping of fresh peripheral blood mononuclear cells from patients with primary HIV infection was performed at baseline. All patients were then followed up every 3 months and the development of solid or hematological malignancies was noted. Results: A total of 155 patients were included in the study and the median follow-up period was 64 months. Treg counts were significantly higher among males, patients with high viral load (>350 copies/ml) and patients with virological failure to antiretroviral treatment (ART). Linear regression analysis showed a significant negative correlation between Treg levels and CD4 (+) T-cell counts. Patients with neoplasia had lower levels of Tregs while increasing levels showed a negative correlation with the development of neoplasia. Conclusion: In our population of HIV-infected patients, high levels of Tregs were associated with disease progression, and low baseline levels were associated with a higher probability of developing neoplasia.
Keywords: cancer